2012
DOI: 10.1097/jom.0b013e3182717cf2
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Health Promotion Implementation, Readiness, and Capacity Among Midsize Employers in Low-Wage Industries

Abstract: Objective To describe workplace health promotion (WHP) implementation, readiness, and capacity among mid-sized employers in low-wage industries in the United States. Methods A cross-sectional survey of a national sample of mid-sized employers (100–4,999 employees) representing five low-wage industries. Results Employers’ WHP implementation for both employees and employees’ spouses and partners was low. Readiness scales showed that employers believe WHP would benefit their employees and their companies, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 37 publications
2
86
0
Order By: Relevance
“…20 They found that the capacity of small employers to implement worksite health promotion was very low. The average capacity score (measure assessing capacity to implement a program) was 0.6 (0 to 3 range) and 1.08 for medium-sized employers.…”
Section: Resultsmentioning
confidence: 99%
“…20 They found that the capacity of small employers to implement worksite health promotion was very low. The average capacity score (measure assessing capacity to implement a program) was 0.6 (0 to 3 range) and 1.08 for medium-sized employers.…”
Section: Resultsmentioning
confidence: 99%
“…industries, even when employers agreed that workplace health-promotion programs might benefit them, they were less likely to agree that implementation of workplace health-promotion programs was feasible (29).…”
Section: Wwwannualreviewsorg • Health Promotion In Smaller Workplacesmentioning
confidence: 98%
“…Similarly, definitions vary for medium-sized workplaces. Recent national surveys have used upper limits of 750 (46), 999 (14), and 4,999 employees (29). In this review, we define small and medium-sized workplaces as having 1,000 or fewer employees and, for the sake of brevity, refer to them collectively as smaller workplaces.…”
Section: Definitions Of Smaller Workplaces and Workplace Health Promomentioning
confidence: 99%
See 1 more Smart Citation
“…(1318) Results from these studies suggest that organizational factors such as company size, industrial sector, existence of top leadership support for OSH or WHP programs, and organizational capacity, in terms of dedicated staff, budgets, and committees to implement OSH and WHP are of potential importance. (1922)…”
Section: Background/objectivesmentioning
confidence: 99%